Hayek, Local Information, and the Decentralization of State-Owned Enterprises in China - Huang, Zhangkai; Li, Lixing; Ma, Guangrong; Xu, Lixin Colin (World Bank, Washington, DC, 2015)
Hayek argues that local knowledge is a key for understanding whether production should be decentralized. This paper tests Hayek’s predictions by examining the causes of the Chinese government’s decision to decentralize state-owned enterprises. Since the government located closer to a state-owned enterprise has more information over that enterprise, a greater distance between the government and the enterprise should lead to a higher likelihood of decentralization. Moreover, where communication costs and the government’s uncertainty over an enterprise’s performance are greater, the government is more likely to decentralize enterprises so that it can better utilize local information. This paper finds empirical support for these implications.